Apoptotic, Cytotoxic and Antimigratory Activities of Phenolic Compounds - Yuce, H.; Sahin, Y.; Turkmen, N. Basak; Ozek, D. Askin; Unuvar, S.; Ciftci, O. (Pleiades Publishing Ltd, 2022)
The objective of this study was to evaluate the biological activities of chrysin (CRY), curcumin (CUR), and ellagic acid (EA) by comparing the anti-proliferative, anti-migration effects, and apoptotic gene expressions between the three human cancer cell lines: lung (A549), liver (HEP3B), and breast (MCF-7) compared to normal human fibroblast cell line (L929). Antiproliferative effects of certain phenolic compounds were determined by the MTS assay. Cells were treated with different concentrations of the compounds for two consecutive days. Their effect on cell migration was evaluated using the wound-healing assay. Apoptosis was evaluated by Bax, Bcl-2, Cas-3, Cas-8, Cas-9, Cas-10, CDK 2, CDK4, CDK6, CCNB1, and CCND2 gene expressions. The MTS assay showed that the compounds had antiproliferative effects on A549, HEP3B, and MCF-7 cell lines in a dose- and time-dependent manner. All three compounds also suppressed the migration of the tumor cell lines, significantly increased the levels of apoptotic gene expression, and induced apoptotic cell death. This study shows that chrysin, curcumin, and ellagic acid could be considered promising chemotherapeutic agents in the treatment of lung, liver, and breast cancers.
Keywords: chrysin; curcumin; ellagic acid; apoptosis; antiproliferative effect; cell migration; lung cancer; hepatoma; breast cancer; fibroblasts